Plasma thiobarbituric acid reactive substances, vitamin A and vitamin E levels and resumption of postpartum ovarian activity in dairy cows. (8th February 2014) - Aoki, Mari; Ohshita, Tomoko; Aoki, Yasuhiro; Sakaguchi, Minoru
Abstract Vitamins with antioxidative functions are commonly used as supplements to improve fertility in dairy cows. However, according to field test results uncertainty exists about the effect of these vitamins, especially in vitamin A and vitamin E, on ovarian functional activity. This study was performed to reveal the physiological characteristics of cows receiving enough feed and the ovaries of which were activated in the early postpartum period. Six of 12 primiparous cows showing the corpus luteum on 25 to 27 days after parturition were classified as early responders (PER); the remaining six were classified as late responders (PLR). Among 11 multiparous cows, nine were early responders (MER), and the remaining two were late responders (MLR). Plasma concentration of thiobarbituric acid reactive substances (TBARS) in the PER were lower than those in the PLR (P < 0.01). The ratio of plasma all‐trans‐retinol to intake α‐tocopherol or β‐carotene were increased in the following order: MER < PER < PLR (P < 0.01). The milk lactose (P < 0.025) and plasma glucose (P < 0.01) of the early responders tended to be lower than those of the late responders. These may have been associated with the availability of vitamins or energy balance. Thus, we suggest the possibility that the cows which were able to utilize antioxidants and energy from the feed efficiently may have earlier resumption of ovaries postpartum.